Spatially directed vesicle capture in the ordered pores of breath-figure polymer films1. Issue 26 (14th July 2015) - Arora, J. S.; Ponnusamy, T.; Zheng, R.; Venkataraman, P.; Raghavan, S. R.; Blake, D.; John, V. T.
<x xml:space="preserve">Abstract</x> A hydrophobically modified biopolymer (chitosan) when deposited in the pores of patterned polymeric breath figures insets its hydrophobes into liposomal bilayers. This is a facile method to capture and tether liposomes in a patterned porous polymer film.